Association of Acute Kidney Injury with Bronchopulmonary Dysplasia in Preterm Infants - Saime Hacer OZDEMIR; Husnu Fahri OVALI (Medeniyet Medical Journal)
Objective: Bronchopulmonary dysplasia (BPD) is among the most common complications of prematurity and is associated with high morbidity and mortality rates. Acute kidney injury (AKI) is also commonly observed in premature infants and significantly increases morbidity and mortality. Studies have shown that systemic changes in AKI may also trigger lung damage. Methods: This study aimed to determine the effects of AKI on the development of BPD in preterm infants with a postconceptional age of ≤32 weeks and/or birth weight of ≤1500 grams. The relationship between demographic features and accompanying perinatal and postnatal morbidities among the patients was investigated. Results: The incidence of BPD in infants with AKI was 52.6% (10 of 19 infants) and 38.3% (61 of 140 infants) in infants without AKI. In infants who developed BPD, the rate of AKI did not vary notably between babies born at ≤28 weeks and those born at >28 weeks [n=9, 17.3% (9 of 52 infants) and n= 1, 5.3%, (1 of 19 infants) respectively] of gestation (p>0.05). Conclusions: AKI was associated with a greater need for resuscitation at birth, a greater need for invasive mechanical ventilation, fewer ventilatorfree days, and a higher incidence of sepsis, patent ductus arteriosus, and necrotizing enterocolitis in premature infants. It was also more frequently associated with fluid-electrolyte imbalance, blood pressure, and hemodynamic disorders in the first postnatal week. The rate of BPD development was higher in infants with AKI, but this disparity was not statistically notable (p>0.05).